2019
DOI: 10.3390/cells8020168
|View full text |Cite
|
Sign up to set email alerts
|

CVm6A: A Visualization and Exploration Database for m6As in Cell Lines

Abstract: N6-methyladenosine (m6A) has been identified in various biological processes and plays important regulatory functions in diverse cells. However, there is still no visualization database for exploring global m6A patterns across cell lines. Here we collected all available MeRIP-Seq and m6A-CLIP-Seq datasets from public databases and identified 340,950 and 179,201 m6A peaks dependent on 23 human and eight mouse cell lines respectively. Those m6A peaks were further classified into mRNA and lncRNA groups. To better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…Although most of the m 6 A studies focused on its role in mRNA function, recent reports showed that m 6 A may also regulate ncRNAs functions [17]. Similarly to mRNAs, lncRNAs are also dynamically m 6 A methylated and the modification levels depend on the cell line, tissue type and growth conditions [41,42]. In this study, we focused on potentially m 6 A-regulated lncRNAs with impact on PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the m 6 A studies focused on its role in mRNA function, recent reports showed that m 6 A may also regulate ncRNAs functions [17]. Similarly to mRNAs, lncRNAs are also dynamically m 6 A methylated and the modification levels depend on the cell line, tissue type and growth conditions [41,42]. In this study, we focused on potentially m 6 A-regulated lncRNAs with impact on PCa.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the possibility that m6A regulates the function of HOTAIR in a mechanism similar to its regulation of lncRNA Xist, we investigated previous studies in human cells where m6A sites have been mapped genome wide. We searched the CVm6A database 25 to identify any previously mapped sites of m6A modification in HOTAIR. HOTAIR contains 3 m6A peaks mapped in HeLa cells, although the enrichment score is low for these sites ( Figure S1).…”
Section: Hotair Contains Multiple Sites Of M6a Modification In Breastmentioning
confidence: 99%
“…The m6A methylation landscape of human lncRNAs is essentially different from that of mRNA. It is reported that the average enrichment scores of lncRNAs were similar to those of mRNA in cell lines, but the number of m6A peaks distributed in lncRNAs is significantly lower than those in mRNAs [ 53 ]. In human fetal tissue, lncRNAs were less methylated than mRNAs with an average of 21%.…”
Section: M6a Modification In Different Non-coding Rnasmentioning
confidence: 99%